Tanggung Jawab Pelaku Usaha terhadap Harga Eceran Obat yang Dijual Kepada Konsumen Melebihi Harga Standar - I Kadek Bayu Antara; I Nyoman Gede Sugiartha; Desak Gde Dwi Arini (Jurnal Preferensi Hukum, 2022)
Setting a standard retail price on drug packaging is something that must be done for every drug maker, if the product packaging does not state the standard retail price or when buying and selling takes place does not heed the contents of the relevant law, the government will carry out guidance and supervision of drug maker or seller. The purposes of this study are to reveal the protection of drug consumers who consume drugs whose prices exceed the standard retail price and the responsibility of business actors to the retail prices of drugs sold to consumers that exceed the standard price. This type of research uses a normative legal research type with a case and legislation approach. The sources of legal materials used by the author are primary and secondary legal materials with inventory collection techniques presented in qualitative form. The results of the study reveal that legal protection for consumers against the retail price of drugs sold to consumers exceeds the standard price is divided into two, namely preventive legal protection and repressive legal protection. The responsibility of the drug seller who exceeds the standard retail price is to provide compensation, either in the form of a refund for the purchase of drugs, giving exchange for drugs that have the same use which is equivalent in price. The provision of compensation must be carried out for a maximum of 7 (seven) which starts from the time the sale and purchase agreement occurs.